The Potentials of New Work Environment for Dynamic Workforce in the 21st Century of Malaysia Context - Leong , Yin Chen; Sharif, Roslina (MAJ - Malaysia Architectural Journal, 2020)
As the world of work is in constantly changed, new technologies and behaviours are introduced to our organization. In order to fulfil the personality’s character, economic needs and individual needs, the global workforce is now becoming more dynamic due to this randomness. The new dynamic workforce required a different demand for working environment as the current traditional workforce and the contemporary workforce is no longer able to fulfil the current needs or facilitate the new workforce environment. Nowadays, people are working in a disorganized, scattered and no collective workforce environment. There are no support systems or facilities to solve the issue which lead to a decrease in productivity. Hence, to increase productivity, new support system, facilities or community play an essential role in this matter. The paper aims to identify the potentials of a new work environment for a dynamic workforce and provide suggestion and interventions for a dynamic workplace. The article included studies published by various authors, books and journals. The data will be gathered through the questionnaire, which has been distributed to targeted audiences such as freelancer, remote worker, nomadic worker and others who are determined to be the dynamic workforce in this study. Furthermore, the data results have been carefully collected, analysed and concluded. The outcome will help create a better understanding of the potentials of the new work environment for the dynamic workforce, which can be used as a guide for any development of a new work environment in the future.